2015
DOI: 10.4103/0971-5851.158842
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor-β1 and TGF-β2 act synergistically in the fibrotic pathway in oral submucous fibrosis: An immunohistochemical observation

Abstract: Background and objectives:Oral Submucous Fibrosis (OSF) is a potentially malignant oral disorder which leads to fibrosis of the oral mucosa and has a high rate of malignant transformation. The consumption of various forms of areca nut is causatively linked to the condition. The constituents of areca nut activate several pro-fibrotic cytokines, chiefly transforming growth factor-β1, β2, which leads to an increased deposition and decreased degradation of extracellular matrix and collagen. TGF-β1, β2 probably rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…As shown by authors, members of the TGF-β family of cytokines distinguish CAFs from oral cancer and from normal oral fibroblasts [ 28 ]. In other studies, the researchers investigated the role of TGF-β in the induction of fibrosis in another oral disorder, namely oral submucous fibrosis (OSF) [ 29 , 30 ]. OSF is a potentially malignant condition of the oral cavity, characterized by a generalized submucosal fibrosis [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown by authors, members of the TGF-β family of cytokines distinguish CAFs from oral cancer and from normal oral fibroblasts [ 28 ]. In other studies, the researchers investigated the role of TGF-β in the induction of fibrosis in another oral disorder, namely oral submucous fibrosis (OSF) [ 29 , 30 ]. OSF is a potentially malignant condition of the oral cavity, characterized by a generalized submucosal fibrosis [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Isoforms of TGF-β , β1 and β2 have been defined as a pro-fibrotic growth factors which cause deposition of extracellular matrix (ECM) by increasing the synthesis of matrix protein like collagen and decreasing the degradation by stimulating various inhibitor mechanisms. As detailed by Kamath et al, expression of TGF-β1 and TGF-β2 was increased in OSF as compared to normal oral mucosa [ 29 ]. Additionally, authors have shown the most prominent role of isoform β1 in the fibrotic pathway.…”
Section: Discussionmentioning
confidence: 99%
“…This also explains the highest TGF-β1 and α-SMA immunoexpression in the submucosa in advanced OSMF grades. 18,19…”
Section: Discussionmentioning
confidence: 99%
“…[20] A profibrotic factor -TGF-β1-has been shown to play a crucial role in the pathophysiology of fibrotic diseases such as pulmonary fibrosis, oral submucosal fibrosis, systemic sclerosis, renal fibrosis and Peyronie's disease. [21][22][23][24] Besides, TGF-β1 was proven to create fibrosis of the urethra in several animal studies. [25,26] These data may indicate a correlation between platelet counts and TGF-β1 levels.…”
Section: Discussionmentioning
confidence: 99%